2016
DOI: 10.1111/jog.13041
|View full text |Cite
|
Sign up to set email alerts
|

Background of couples undergoing non‐invasive prenatal testing in Japan

Abstract: Knowing the specific backgrounds of couples who have undergone NIPT may be important for improving the quality of genetic counseling for NIPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…If the results of NIPT are negative for a twin pregnancy, the pregnant woman and her family are likely to relieved. We previously reported that women who undergo NIPT tend to have high levels of mental distress, because of the higher proportions of women with an advanced maternal age and women using ART . Additional studies examining the use of NIPT for twin pregnancies should be conducted, because the risk of miscarriage as a result of prenatal testing is higher for twin pregnancies than for singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…If the results of NIPT are negative for a twin pregnancy, the pregnant woman and her family are likely to relieved. We previously reported that women who undergo NIPT tend to have high levels of mental distress, because of the higher proportions of women with an advanced maternal age and women using ART . Additional studies examining the use of NIPT for twin pregnancies should be conducted, because the risk of miscarriage as a result of prenatal testing is higher for twin pregnancies than for singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the proportion of pregnant women with ART at our center (33.9%) was higher than the national average (5.5%) 12,13 . It was reported that pregnant women who received reproductive assistance preferred to undergo prenatal GT 14 …”
Section: Discussionmentioning
confidence: 72%
“…Pregnant Japanese women reportedly have positive attitudes toward NIPT, and the demand for genetic counseling for pregnant women undergoing NIPT is expected to increase in the near future. Pregnant women in this study who underwent NIPT tended to have greater age differences from their spouse and had conceived via ART . It is important to identify pregnant women with a high risk of depression during pregnancy and genetic counseling for NIPT may assist women with depressive symptoms.…”
Section: Resultsmentioning
confidence: 97%
“…Pregnant women in this study who underwent NIPT tended to have greater age differences from their spouse and had conceived via ART. 22 It is important to identify pregnant women with a high risk of depression during pregnancy and genetic counseling for NIPT may assist women with depressive symptoms. Although women may not feel mental stress before undergoing NIPT, they may develop mental distress post-partum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation